Successful staged repair for a rare type of truncus arteriosus with interruption of the aortic arch and abnormal origin of the left coronary artery - Uchita, Shunji (BioMed Central, 2013)
We report a successful staged repair for a quite rare combination of truncus arteriosus (TA), Van Praagh type A4, and abnormal origin of the left coronary artery (CA). Furthermore, the case was complicated by a variant of the chromosomal anomaly in cat-cry syndrome. The presence of interruption of the aortic arch (IAA) and abnormal CA origin has been previously reported to increase mortality. To decrease the risk of bronchomalacia in infants, bilateral pulmonary artery banding (PAB) was performed as the first stage procedure for adjusting the pulmonary flow. Staged repair is a useful strategy for infants with complex TA.